Synergistic Antioxidant Activity of Four-Component Mixture of Essential Oils: Basil, Cedarwood, Citronella and Thyme for the Use as Medicinal and Food Ingredient - Tomasz Baj; Grażyna Kowalska; Radosław Kowalski; Jolanta Szymańska; Guoyin Kai; Henrique Douglas Melo Coutinho; Elwira Sieniawska (MDPI AG, 2023)
Mixture design is a statistical tool used to obtain the maximum desired effect using the minimum number of experiments. The aim of the presented work was the optimization of the composition of a mixture of essential oils from basil, citronella, cedarwood and thyme using simplex-lattice mixture design method. The optimized parameter was an antioxidant activity measured in DPPH assay and expressed as effective concentration (EC50). The test results showed an interesting synergy between the components of essential oils. The prepared binary and quaternary mixtures were characterized by higher activity than simple average activity. The designed mixture with approximated highest antioxidant activity was composed of: 54.4% citronella essential oil, 33.0% thyme essential oil, 9.2% cedarwood essential oil and 3.4% basil essential oil and its approximated activity was in agreement with experimental values. This work confirmed that it is possible to approximate the best antioxidant composition of four essential oils used as a potential medicinal and food ingredient.